STRATEGIES FOR INNOVATIVE LEARNING BASED ON ISLAMIC VALUES IN THE DIGITAL ERA - Abdillah, Ikhwan; Nugraha, Lukman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines innovative strategies in Islamic education learning based on digital technology and identifies the challenges and opportunities in integrating Islamic values into digital learning. The methodology used in this research is a literature review with a qualitative approach, where the author examines various literatures related to the application of technology in Islamic education and its impact on the development of student character. Data analysis is conducted by comparing findings from relevant sources. The research results show that digital technology has great potential to enhance learning effectiveness, but there are challenges in maintaining the balance between utilising technology and preserving Islamic values. Furthermore, integrating Islamic values into technology-based learning can strengthen student character and develop 21st-century skills such as critical thinking and collaboration. This study concludes that the application of technology in Islamic education should be carried out wisely while emphasising the moral and spiritual values that form the foundation of student character development.